2007
DOI: 10.1089/apc.2006.0079
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Primary Antiretroviral Resistance Genotypic Mutations And B/F Recombinants in Santos, Brazil

Abstract: This study characterized HIV-1 among antiretroviral-naïve populations presenting recent infection (RI) or long-standing infection (LSI). Sera collected from January 1999 to December 2001 at an anonymous HIV testing site in Santos, Brazil, were submitted to serologic testing algorithm for recent HIV seroconversion (STARHS). The STARHS methodology uses a combination of a sensitive and a less sensitive version of an anti-HIV enzyme immunoassay (EIA), and specimens found to be positive on the sensitive EIA and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
46
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 83 publications
(83 reference statements)
8
46
0
4
Order By: Relevance
“…The prevalence of pDRM was similar to most of the studies in the country (Brindeiro et al 2003, Barreto et al 2006, Rodrigues et al 2006, Brigido et al 2007, EyerSilva et al 2008), but some studies showed higher rates (Pedroso et al 2007, Sucupira et al 2007). These studies varied in patient population selection, type of genetic material analysed and the list of mutations considered for surveillance purposes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of pDRM was similar to most of the studies in the country (Brindeiro et al 2003, Barreto et al 2006, Rodrigues et al 2006, Brigido et al 2007, EyerSilva et al 2008), but some studies showed higher rates (Pedroso et al 2007, Sucupira et al 2007). These studies varied in patient population selection, type of genetic material analysed and the list of mutations considered for surveillance purposes.…”
Section: Discussionsupporting
confidence: 82%
“…These studies varied in patient population selection, type of genetic material analysed and the list of mutations considered for surveillance purposes. The study with higher levels of resistance was based on proviral DNA (Sucupira et al 2007), whereas most of the other studies were based on HIV-1 virion RNA. Few studies have compared plasma and cell mutation profiles, but cell/plasma discordance is not uncommon (Bon et al 2007) and one recent study suggested an astonishingly high degree of heterogeneity among peripheral blood mononuclear cells (PBMCs) in regards to resistance (Quan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The L10I/V polymorphism is a mutation that is weakly associated with a reduced response of the virus to some PIs 26 . The combination of minor mutations M36I and L10I/V has been suggested to result in the subsequent development of mutation L90M, causing virological failure and some level of resistance to all PIs 29,36 .…”
mentioning
confidence: 99%
“…Up to the present time, this seems not to be the case in Brazil . When compared to figures reported from developed nations, most studies from Brazil have found relatively low rates of primary HIV-1 drug resistance (Brindeiro et al 1999, Dumans et al 2002, Brindeiro et al 2003, Pires et al 2004, Brigido et al 2005, Barreto et al 2006, Medeiros et al 2006, Rodrigues et al 2006, SaFerreira et al 2007, even though isolated surveys recently reported worrisome rates in the port cities of Santos (Sucupira et al 2007) and Salvador (Pedroso et al 2007). Also, resistance rates in Brazil are being reported from studies primarily based in large urban centers and little is known about the prevalence of resistant strains in innermost parts of the country.…”
mentioning
confidence: 97%